Faecal carriage of ESBL producing and colistin resistant Escherichia coli in avian species over a 2-year period (2017-2019) in Zimbabwe - Takawira, Faustinos Tatenda; Pitout, Johann D. D.; Thilliez, Gaetan; Mashe, Tapfumanei; Gutierrez, Ana Victoria; Kingsley, Robert A.; Peirano, Gisele; Matheu, Jorge; Midzi, Stanley Munyaradzi; Mwamakamba, Lusubilo Witson; Gally, David L.; Tarupiwa, Andrew; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Extended spectrum beta-lactamase (ESBL) producing Escherichia coli have become widespread among food producing animals. These strains serve as a reservoir of antibiotic resistance genes (ARGs) and act as a possible source of infection to humans as transmission can occur by direct or indirect contact. Methods This study investigated the faecal carriage of ESBL producing and colistin resistant E. coli in poultry over a 2-year period (2017-2019) from Zimbabwe. A total of 21 ESBL positive isolates from poultry cloacal specimens were selected for whole genome sequencing from animal E. coli isolates bio-banked at the National Microbiology Reference laboratory using phenotypic susceptibility testing results from the National Escherichia coli Surveillance Program to provide representation of different geographical regions and year of isolation. Cloacal swabs were collected from 3000 broiler live birds from farm 1 and from farm 2, 40 backyard chickens and 10 ducks were sampled. Antimicrobial susceptibility and ESBL testing were performed as per Clinical Laboratory Standards Institute guidelines. Whole genome sequencing of ESBL producing isolates was used to determine sequence types (STs), ARGs, and phylogroups. Results Twenty-one of the included E. coli isolates were confirmed as ESBL producers. Three defined sequence type clonal complexes (CCs) were identified (ST10CC, ST155CC and ST23CC), with ST10CC associated with the most antibiotic resistant profile. The ESBL phenotype was linked to the presence of either cefotaximase-Munich-14 (CTX-M-14) or CTX-M-79. Plasmid mediated quinolone resistant determinants identified were qnrB19 and qnrS1 and one ST10CC isolate from farm 1 broiler chickens harbored a mobile colistin resistance gene (mcr-1). Phylogenetic groups most identified were B1, A and unknown. Discussions The avian ESBL producing E. coli belonged to a diverse group of strains. The detection of several ARGs highlights the importance of implementing enhanced control measures to limit the spread in animals, environment, and humans. This is the first report of mcr-1 in Zimbabwe, which further underscores the importance of the One Health approach to control the spread and development of AMR.